TOShKENT VILOYATIDA MAKTABGAChA TAʼLIM TAShKILOTLARINI TAShKIL ETIShDA DEMOGRAFIK OMILNING ROLI - Tojiyeva, Z.; Sabirova, M.; Ruzmanova, D.; Saidova, Z.; Omanova, K. (SCIENCE and SOCIETY, 2025)
This article discusses issues related to changes in the demographic situation in the organization of pre-school educational organizations created in the Tashkent region. The demographic situation in the Tashkent region, problems and ways to solve them are presented.